2017
DOI: 10.1177/1045389x17689943
|View full text |Cite
|
Sign up to set email alerts
|

Metamodel-assisted design optimization of piezoelectric flex transducer for maximal bio-kinetic energy conversion

Abstract: Energy Harvesting Devices (EHD) have been widely used to generate electrical power from the bio-kinetic energy of human body movement. A novel Piezoelectric Flex Transducer (PFT) based on the Cymbal device has been proposed by Daniels et al. (2013) for the purpose of energy harvesting. To further improve the efficiency of the device, optimal design of the PFT for maximum output power subject to stress and displacement constraints is carried out in this paper.Sequential Quadratic Programming (SQP) on metamodels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It can be seen that the proposed multi-level surrogate modeling strategy for design optimization of piezoelectric energy- harvesting devices improves not only the accuracy of the predictions but also the performance of the device. In order to demonstrate the superiority of the proposed multi-level surrogate modeling strategy over other optimization methodologies used in the previous work (Forrester and Keane, 2009;Luo et al, 2017), the optimal designs including optimal solution of the multi-level surrogate modeling strategy, the singlesingle level surrogate modeling approach, and the conventional varying one parameter a time optimization technique are listed and compared in Table 4. Where a safety factor of 2.0 is applied to the stress constraint.…”
Section: Optimal Results and Validation By Fe Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the proposed multi-level surrogate modeling strategy for design optimization of piezoelectric energy- harvesting devices improves not only the accuracy of the predictions but also the performance of the device. In order to demonstrate the superiority of the proposed multi-level surrogate modeling strategy over other optimization methodologies used in the previous work (Forrester and Keane, 2009;Luo et al, 2017), the optimal designs including optimal solution of the multi-level surrogate modeling strategy, the singlesingle level surrogate modeling approach, and the conventional varying one parameter a time optimization technique are listed and compared in Table 4. Where a safety factor of 2.0 is applied to the stress constraint.…”
Section: Optimal Results and Validation By Fe Simulationsmentioning
confidence: 99%
“…The PFT was manufactured and experimentally tested, the results of which were used for validation of FE models, including the one used in this article. Luo et al (2017) successfully applied the metamodeling technique to obtain an optimal design of the PFT device by parametric optimization. The optimal design offered a power output of 6.54 mW, representing an improvement of more than 58% as compared to the power output of 4.13 mW from the original PFT design when a safety factor of 2.0 is applied.…”
Section: Coupled Piezoelectric Fe Modelmentioning
confidence: 99%
“…Among those introduced optimization techniques, metamodeling based algorithms show advantages of high efficiency compared to stochastic algorithms and more general applicability, given problems where the gradient information is nontrivial to calculate [16]. Metamodeling has a broad application in simulation-based optimization, where the simulation is treated as numerical experiments [1,17,18]. Meanwhile, the computational cost may be reduced dramatically [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, GP has been widely reported to be successfully applied in developing analytical expression for cold-formed steel, 15 deformation modulus of rock, 16 torsional strength of concrete beam 17 and the bond strength of carbon fibre reinforced polymers (CFRPs). 18 In addition, LHS (Latin Hypercube sampling) and GP coupled techniques were used in studies 19,20 to predict the principal stress of a piezoelectric flex transducer, where successful new design was obtained based on the developed method. In these studies, the GP method demonstrated its significant advantage in high prediction accuracy over empirical equations, conventional design codes and traditional multiregression methods.…”
Section: Introductionmentioning
confidence: 99%